GABAergic integration of transient and persistent neurons in the developing mouse somatosensory cortex - Abusaada, Ahd; De Rosa, Federico; Luhmann, Heiko J.; Kilb, Werner; Sinning, Anne (Frontiers in Cellular Neuroscience, 2025)
GABA is an essential element in the function of neocortical circuits. The origin, migration and mechanisms of synaptogenesis of GABAergic neurons have been intensively studied. However, little information is available when GABAergic synapses are formed within the different cortical layers, neuronal cell types and subcellular compartments. To quantify the distribution of GABAergic synapses in the immature somatosensory mouse cortex, GABAergic synapses were identified by spatially coincident immunoprofiles for the pre- and postsynaptic markers vGAT and gephyrin at postnatal days (P)0-12. Between P0-5, GABAergic synapses are mainly restricted to the marginal zone, while at later developmental stages a more homogenous distribution is obtained. Cajal-Retzius neurons represent a major target of GABAergic synapses in the marginal zone with a homogeneous synapse distribution along the dendrite. The number of GABAergic synapses per pyramidal neuron increases substantially between P0 and P12, with a stable density and distribution in basal dendrites. In contrast, along apical dendrites synapses accumulate to more proximal positions after P8. Overall, the results of this study demonstrate that early GABAergic synaptogenesis is characterized by a consistent increase in the density of synapses with first a stringent overrepresentation in the marginal zone and a delayed establishment of perisomatic synapses in pyramidal neurons.